Examining therapeutic alliance, adherence, and dropout in brief telepsychotherapy: A qualitative study - Martins, Dayane Santos; Viduani, Anna; Dreher, Carolina Blaya; Salum, Giovanni; Manfro, Gisele Gus (Journal of counseling psychology, 2025)
The complexity of therapeutic processes has been the subject of extensive research, encompassing both evidence-based techniques and protocols, as well as the more subjective aspects of therapy. These subjective aspects include the fundamental competencies of the therapist and the crucial establishment of a strong therapeutic alliance (TA). The TA-a sine qua non factor for improved outcomes-remains underexplored in certain contexts. This study aimed to explore the role of the TA within a brief cognitive-behavioral teletherapy protocol designed for crisis settings. Using framework analysis, we transcribed and analyzed 20 psychotherapy sessions involving 20 distinct therapeutic dyads. For these, we included 10 dyads of clients who dropped out and 10 of those who completed treatment. One key finding was that client engagement improved when their needs were effectively addressed through the protocol, aligning with the establishment of clear therapy goals, a core component of the TA. In contrast, therapists who adopted a more directive or hierarchical approach in delivering interventions tended to foster weaker alliances, which might have contributed to higher rates of therapy dropout. We discuss how the identified themes influence the TA and psychotherapy outcomes, offering insights to support the development of tailored treatment strategies. Improving goal alignment between therapists and clients can enhance the effectiveness of mental health care. This is particularly critical in the context of brief psychotherapies, which must balance effectiveness with responsiveness to clients' immediate needs in response to crises. (PsycInfo Database Record (c) 2025 APA, all rights reserved).